Implementation of Taguchi Method in Optimizing Virgin Coconut Oil Extraction by Cooling and Centrifugation Techniques - Andivas, Marulan; Kisanjani, Alex; Kurnia, Wahyu Ismail; Febryantri, Novia (Performa: Media Ilmiah Teknik Industri, 2000)
Virgin Coconut Oil (VCO) extraction through refrigeration and centrifugation techniques has become the preferred extraction technique due to its ability to maintain oil quality. However, optimization of extraction yield and quality remains a challenge. Therefore, this study aims to identify the optimal factors in VCO extraction, focusing on yield and physicochemical quality, through the application of the Taguchi method. The factors tested included centrifugation speed, centrifugation time, storage temperature, and storage duration, each with three levels, using an orthogonal array L9(3^4). In addition, analysis of variance (ANOVA) was used to investigate the effects and contributions of each aspect. The experimental results indicated that centrifugation speed and storage temperature had significant effects on VCO yield, while centrifugation time and storage duration had minimal effects. Analysis of Variance (ANOVA) confirmed that centrifugation speed contributed 88.31% and storage temperature 7.68% to the yield. For the quality parameters of VCO content, such as moisture content, free fatty acids, total acid number, and peroxide value, no factor significantly affected the quality of VCO, indicating that this method is effective in maintaining quality under various conditions. These findings suggest that optimization of centrifugation speed and storage temperature can increase VCO yield without compromising quality. This research contributes to providing practical insights for efficient and high-quality VCO production, in accordance with the Indonesian National Standard (SNI 7381:2022) for VCO quality. Furthermore, VCO producers, including micro and small scale businesses, can produce large scale and consistent VCO without having to reduce product quality by optimizing centrifugation speed and storage temperature during the VCO manufacturing process.